Mitosis of hepatitis B virus-infected cells in vitro results in uninfected daughter cells - Tu, Thomas; Zehnder, Benno; Wettengel, Jochen M.; Zhang, Henrik; Coulter, Sally; Ho, Vikki; Douglas, Mark W.; Protzer-Knolle, Ulrike; George, Jacob; Urban, Stephan (JHEP reports, 2022)
Background & Aims - The chronicity of HBV (and resultant liver disease) is determined by intrahepatic persistence of the HBV covalently closed circular DNA (cccDNA), an episomal form that encodes all viral transcripts. Therefore, cccDNA is a key target for new treatments, with the ultimate therapeutic aim being its complete elimination. Although established cccDNA molecules are known to be stable in resting hepatocytes, we aimed to understand their fate in dividing cells using in vitro models. - Methods - We infected HepG2-NTCP and HepaRG-NTCP cells with HBV and induced mitosis by passaging cells. We measured cccDNA copy number (by precise PCR assays) and HBV-expressing cells (by immunofluorescence) with wild-type HBV. We used reporter viruses expressing luciferase or RFP to track number of HBV-expressing cells over time after mitosis induction using luciferase assays and live imaging, respectively. - Results - In all cases, we observed dramatic reductions in cccDNA levels, HBV-positive cell numbers, and cccDNA-dependent protein expression after each round of cell mitosis. The rates of reduction were highly consistent with mathematical models of a complete cccDNA loss in (as opposed to dilution into) daughter cells. - Conclusions - Our results are concordant with previous animal models of HBV infection and show that HBV persistence can be efficiently overcome by inducing cell mitosis. These results support therapeutic approaches that induce liver turnover (e.g. immune modulators) in addition to direct-acting antiviral therapies to achieve hepatitis B cure. - Lay summary - Chronic hepatitis B affects 300 million people (killing 884,000 per year) and is incurable. To cure it, we need to clear the HBV genome from the liver. In this study, we looked at how the virus behaves after a cell divides. We found that it completely clears the virus, making 2 new uninfected cells. Our work informs new approaches to develop cures for chronic hepatitis B infections.
Gesehen am 03.03.2023